Analysis of volumetric properties of liquid mixtures: I. method of binary additive quasi-solvates - Pavel Efimov (Вісник Харківського національного університету: Серія xімія)
The method of binary additive quasi-solvates (BAQS) a new approach for analyzing the physicochemical properties of solutions is proposed. Quasi-solvate Qij is a hypothetical two-particle structure in which one particle i is the ‘solute’ and the other particle j is the ‘solvent’. A set of similar quasi-solvates has the macroscopic property Fij. The solution is an additive mixture of quasi-solvates with weight functions wij. Two models have been developed within the BAQS method: with symmetric weight functions (BAQS/S) and with asymmetric weight functions (BAQS/A). On the example of volumetric properties of non-electrolyte solutions the possibilities of the method are shown. Effective limiting partial molar volumes of components for mixtures of non-electrolytes are determined. The possibility of predicting the properties of multicomponent solutions from data for two-component systems is considered. Applications to other solution properties are shown. Each of the proposed models has its own advantages and limitations.